Index, 2016, Vol. 5, N. 1 - ADCAIJ ADCAIJ (Advances in Distributed Computing and Artificial Intelligence Journal, 2016)
ADCAIJ: Advances in Distributed Computing and Artificial Intelligence Journal, 2016, Vol. 5, N. 1, pp. I-II.